Jean Pidoux, Des fontaines de Pougues en Nivernais… (1584) - Francesca Canadé Sautman (Histoire, Médecine et Santé, 2023)
The use of curative baths, known in Europe since the Middle Ages, especially in Italy, increased in France after the mid-16th century, but texts extolling the virtues of local springs were still rare, hence the importance of Jean Pidoux’s (1550?-1610) treatise on the therapeutic fountains of Pougues, published in 1584. As physician to the Duke of Nevers, Pidoux promoted their medicinal cold waters -- the first of their kind to be renowned in France -- to the court and aristocracy. These waters, intended for drinking cures, were often compared to those of the town of Spa. Pidoux contrasts Spa with his “regional cure,” from cold to hot, starting in Pougues. Like other contemporary scientific treatises, Pidoux’s treatise was written in French, helping to spread medical knowledge more widely. His spa regime incorporated many aspects of Italian treatises, and he was the first to advocate the widespread use of showers in France, imitating the Italian practice.